PENGARUH WORK LIFE BALANCE DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA BADAN PUSAT STATISTIK (BPS) PESAWARAN - Septiandi, Rachmat; Helmita; Loliyani, Rini (Jurnal Bisnis Darmajaya, 2025)
This research analyzes how work-life balance and work-related stress influence employee performance at the Pesawaran Central Statistics Agency (BPS). The study was conducted in response to growing work demands that may affect employee performance through psychological and organizational conditions. A quantitative survey approach was employed by involving all 35 employees using a saturated sampling technique. Data were obtained through structured questionnaires that had been tested and confirmed to be valid and reliable. The data were analyzed using multiple linear regression, preceded by classical assumption testing. The results reveal that work-life balance contributes positively and significantly to employee performance, while work stress does not show a significant individual effect. Nevertheless, when examined simultaneously, both variables significantly affect performance. These findings indicate that strengthening work-life balance policies, accompanied by appropriate stress management, is essential for maintaining a productive and stable work environment.